1998
DOI: 10.1111/j.1553-2712.1998.tb02780.x
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic Judgment of the Need for Trauma Team Activation for Pediatric Patients

Abstract: Abstract. Objective: To determine the value of paramedic judgment in determining the need for trauma team activation (TTA) for pediatric blunt trauma patients. Methods: A prospective, observational study was conducted a t the ED of Children's Hospital Medical Center of Akron between July 12, 1996, and February 28,1997, in cooperation with Akron Fire Department emergency medical technician-paramedics (EMT-Ps). The ED provides on-line and off-line medical control for pediatric transports. Patients with minor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 22 publications
0
31
1
Order By: Relevance
“…14 In contrast to our findings, a number of studies found that paramedic judgment was an inferior method to other criteria for identifying injury severity. 10,11,13,16 The conflicting results related to paramedic judgment may be caused by differences in the trauma populations studied, emergency medical service and trauma systems, research methodologies, and outcome measures. There are a number of different definitions for evaluating trauma triage methods, with no consensus on a gold standard.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…14 In contrast to our findings, a number of studies found that paramedic judgment was an inferior method to other criteria for identifying injury severity. 10,11,13,16 The conflicting results related to paramedic judgment may be caused by differences in the trauma populations studied, emergency medical service and trauma systems, research methodologies, and outcome measures. There are a number of different definitions for evaluating trauma triage methods, with no consensus on a gold standard.…”
Section: Discussionmentioning
confidence: 94%
“…2,12,14,17 Others found their ability to reliably identify overall injury severity a relatively poor indicator. 10,11,13,15,16 These conflicting findings may be partly caused by the variety of different outcome measures used to define injury severity across the studies. The studies also differed in terms of population (adult or pediatric), injury mechanism (blunt or penetrating), emergency medical service systems, and study size, potentially contributing to the conflicting findings.…”
mentioning
confidence: 90%
“…This study points out that criteria for determining the level of activation must take into account over and under triage, both of which may result in a suboptimal patient outcome. Similarly, paramedic judgment in the field alone is not sufficiently sensitive to be of clinical use in defining the need for trauma team activation for pediatric blunt trauma patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have found EMS providers to be accurate in their ability to triage patients, whereas others have found accuracy rates to be unacceptable (2)(3)(4)(5)(6)(7)(8)(9). A number of publications have raised the question of whether paramedics can safely predict if a patient needs transport at all (4,10,11).…”
Section: Introductionmentioning
confidence: 97%